Removal mechanism of decabromodiphenyl ether in soil by Cu/Fe nanoparticles - Siyuan Ling; Ying Han; Shuangqing Hu (Elsevier, 2024)
Decabromodiphenyl ether (BDE-209), a widely used and environmentally significant legacy brominated flame retardant, is frequently found in farmland soil near electronic waste disposal sites and manufacturing facilities. Due to their high adsorption and dehalogenation capabilities, nanoparticles have become a prominent solution for soil remediation. Herein, Cu/Fe bimetallic nanoparticles (BNPs) were prepared and the use of these particles was investigated for the removal of BDE-209 from soil. Optimal conditions, including 9.1 wt% Cu loading and acidic environments, were identified to enhance the removal efficiency. The process involves desorption from soil, adsorption onto BNPs, and subsequent degradation. The contributions of adsorption and degradation were investigated by isolating the BNPs after the experiments conducted herein. Initially, adsorption played an important role, accounting for 25 %-38 % of the total removal, but this decreased to 14 % to 20 % as the reaction progressed, reaching at the equilibrium adsorption capacity after ∼3 h. Notably, hydroxylated polybrominated diphenyl ethers (PBDE) congeners were absent in all soil, BNP, and aqueous solution samples, indicating that stepwise debromination primarily drives the degradation process.